2020
DOI: 10.1038/s41598-020-57838-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-330-3p in Late Pregnancy is Associated with Pregnancy Outcomes Among Lean Women with GDM

Abstract: Gestational Diabetes Mellitus (GDM) is characterised by insulin resistance accompanied by reduced beta-cell compensation to increased insulin demand, typically observed in the second and third trimester and associated with adverse pregnancy outcomes. There is a need for a biomarker that can accurately monitor status and predict outcome in GDM, reducing foetal-maternal morbidity and mortality risks. To this end, circulating microRNAs (miRNAs) present themselves as promising candidates, stably expressed in serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 69 publications
1
58
0
Order By: Relevance
“…Interestingly, in this study there were two subgroups of women with GDM (based on miR-330-3p expression), and the subgroup with relatively higher levels of miR-330-3p had lower fasting insulin and higher incidence of Caesarean section deliveries [49]. In a recent study, higher miR-330-3p levels in the third trimester of pregnancy were reported to be associated with lower exogenous insulin supplementation and better response to GDM management therapy as well as a higher number of vaginal deliveries in women with GDM [50]. The differences observed in the miRNA expression profiles between these different studies could be attributed to type of biofluid, stage of pregnancy for sample collection, ethnicity, age, BMI and smoking status of enrolled participants.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this study there were two subgroups of women with GDM (based on miR-330-3p expression), and the subgroup with relatively higher levels of miR-330-3p had lower fasting insulin and higher incidence of Caesarean section deliveries [49]. In a recent study, higher miR-330-3p levels in the third trimester of pregnancy were reported to be associated with lower exogenous insulin supplementation and better response to GDM management therapy as well as a higher number of vaginal deliveries in women with GDM [50]. The differences observed in the miRNA expression profiles between these different studies could be attributed to type of biofluid, stage of pregnancy for sample collection, ethnicity, age, BMI and smoking status of enrolled participants.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that most of the exosomal circRNAs harbored miRNA-binding sites, and some miRNAs were associated with GDM. For example, miR-330, miR-23a, and miR-16-5p were reported to be up-regulated in the plasma of GDM patients [ 29–32 ]. miR-330, miR-23a and miR-16-5p were matched with circ_0092108, which was verified to down-regulated in umbilical cord blood exosomes of GDM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study through ROC analysis showed that the AUC was 0.927 for miR-185 with a sensitivity and specificity of 0.865 and 0.838, respectively, indicating serum miR-185 differentiated patients with GDM from healthy controls ( 123 ). Moreover, miR-330-3p ( 18 , 24 32 ) was identified as being significantly upregulated in lean women with GDM compared to nondiabetic pregnant women during the third trimester, highlighting miR-330-3p as a possible new biomarker ( 120 ). Furthermore, a significant decrease occurred in the expression levels of miR-21-3p during the third trimester in GDM patients compared with healthy controls, whose AUC in GDM was 0.73 ( 121 ).…”
Section: Clinical Significance Of Non-coding Rnas and Evs For Gdmmentioning
confidence: 99%